2022
DOI: 10.1128/spectrum.02427-21
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Efficient, and Cost-Effective Gene Editing of Enterococcus faecium with CRISPR-Cas12a

Abstract: Enterococcus faecium is increasingly associated with hard-to-treat antibiotic-resistant infections. The ability to generate clean genomic alterations is the first step in generating a complete mechanistic understanding of how E. faecium acquires pathogenic traits and causes disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although CRISPR-Cas has been used for genome editing in a variety of microorganisms, the generation of escapers is a ubiquitous phenomenon. ,,,,, Escapers in CRISPR-Cas limit its applications such as for new antimicrobials based on CRISPR-Cas, though the delivery of the CRISPR-Cas is another bottleneck. In this study, we focused on the CRISPR-Cas9-based gene editing system pEcCas/pEcgRNA established in our previous research, which showed that E. coli MG1655 can survive the DBS generated by Cas9 with a rate of 10 –5 –10 –3 , which is much higher than the acceptable rate (10 –8 ) recommended by the NIH (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Although CRISPR-Cas has been used for genome editing in a variety of microorganisms, the generation of escapers is a ubiquitous phenomenon. ,,,,, Escapers in CRISPR-Cas limit its applications such as for new antimicrobials based on CRISPR-Cas, though the delivery of the CRISPR-Cas is another bottleneck. In this study, we focused on the CRISPR-Cas9-based gene editing system pEcCas/pEcgRNA established in our previous research, which showed that E. coli MG1655 can survive the DBS generated by Cas9 with a rate of 10 –5 –10 –3 , which is much higher than the acceptable rate (10 –8 ) recommended by the NIH (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…A CRISPR-Cas12 system was used to generate clean deletion mutants of ptsHI in E. faecium NCTC7171 as previously described (Chua and Collins 2022 ). Briefly, three inserts, a small RNA promoter driving the CRISPR protospacer RNA, and up- and downstream arms homologous to the flanking regions surrounding the ptsHI were amplified by PCR with primers containing splicing by overlap extension (SOE) PCR-compatible overhang regions (5′- -3′ and 5′- -3′; 5′- -3′ and 5′- -3′; and 5′- -3′ and 5′- -3′, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, CRISPR/Cas12a has been proved to be able to simultaneously edit pyrG, pksP , and kusA genes of Aspergillus aculeatus TBRC 277 (an industrially related cell factory), with an efficiency of up to 40% [ 59 ]. In conclusion, CRISPR/Cas12-mediated microbial genome editing mainly involves in strain improvement, such as the production of valuable steroidal pharmaceuticals [ 58 ] and bioproducts [ 59 ], as well as high-performance chassis [ 60 ], and fundamental research, for instance, the study of plant-fungal interactions [ 61 , 62 ] and the pathogenesis of important opportunistic pathogens [ 63 ] (Table 4 ). For ease of understanding, based on existing reports, CRISPR/Cas12-mediated genome editing was represented in Fig.…”
Section: Crispr/cas12 System Involves In Genome Editing Of Microorgan...mentioning
confidence: 99%